Pengembangan Materi Ajar Menulis Puisi Melalui Media Audio-Visual Pada Siswa Kelas II SD/MI di MIN I Bantul Yogyakarta - Rahmaniatul Fithriyah (AT-TURATS, 2019)
This research aims to develop teaching materials to write poetry through audio-visual media in class II, SD / MI. To produce a product in the form of stage writing poetry in a simple child through audio-visual media in teaching material grade II SD / MI by the Research and Development of simplified, includes three main stages, namely 1) the preliminary study; 2) formulation and product development; 3) validation and product dissemination. Results of this research is the stage of writing poetry through audio-visual media that can be done in three stages: knowing, thinking, feeling. Know is the initial stage of introducing the theme of the poem to be written specified in two phases, namely: pre-foundation phase and foundation plantings. Imagining is the stage after the children turn imagination shown in visual media specified in three phases, namely: Phase reseftivitas, reactivity and productivity. Soaking is the stage where the state according to the image and theme supported by appropriate audio poetry themes detailed in two phases, namely: the implementation phase and exploration.